PENERAPAN MEDIA AUGMENTED REALITY BANGUN RUANG UNTUK MENINGKATKAN KETERLIBATAN DAN HASIL BELAJAR GEOMETRI SISWA KELAS V SDN 26 PAYAKUMBUH - Indah Permata sari, Gintan; Ningsih, Yarisda; Salmaini, Salmaini; Helsa, Yullys (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted to improve students' engagement and mathematics learning outcomes in geometry through the implementation of Augmented Reality (AR) media in Grade V at SDN 26 Payakumbuh. The research employed Classroom Action Research based on the Kemmis and McTaggart model, which consisted of planning, action, observation, and reflection carried out in two cycles. The participants were 31 fifth-grade students. Data were collected through classroom observations, achievement tests, questionnaires, interviews, and documentation. The quantitative data were analyzed descriptively to examine improvements in students' engagement and learning outcomes, while the qualitative data were analyzed through data reduction, data display, and conclusion drawing. The findings showed that integrating AR media into geometry lessons created a more interactive learning experience and encouraged greater student participation throughout the learning process. Students became more confident in expressing ideas, asking and answering questions, collaborating with peers, and completing learning activities. In addition, their understanding of geometric concepts improved, as reflected in the increase in learning achievement and the number of students who reached the expected learning criteria after the implementation of the actions. The improvements made in the second cycle further strengthened students' engagement and supported better learning outcomes. These findings indicate that the use of Augmented Reality media can effectively enhance both student engagement and mathematics learning outcomes in elementary school geometry instruction.